LC‐MS/MS‐based metabolic profiling of Escherichia coli under heterologous gene expression stress. Issue 1 (24th June 2019) - Nadeem, Muhammad S.; Razeeth, Mohammed; Choudhry, Hani M. Z.; Anwar, Firoz; Zamzami, Mazin A.; Murtaza, Bibi N.; Al‐Abbasi, Fahad A. M.; Khan, Mohammad I.; Shakoori, Abdul R.
Abstract: Escherichia coli is frequently exploited for genetic manipulations and heterologous gene expression studies. We have evaluated the metabolic profile of E. coli strain BL21 (DE3) RIL CodonPlus after genetic modifications and subjecting to the production of recombinant protein. Three genetically variable E. coli cell types were studied, normal cells (susceptible to antibiotics) cultured in simple LB medium, cells harboring ampicillin‐resistant plasmid pET21a (+), grown under antibiotic stress, and cells having recombinant plasmid pET21a (+) ligated with bacterial lactate dehydrogenase gene grown under ampicillin and standard isopropyl thiogalactoside (IPTG)‐induced gene expression conditions. A total of 592 metabolites were identified through liquid chromatography‐mass spectrometry/mass spectrometry analysis, feature and peak detection using XCMS and CAMERA followed by precursor identification by METLIN‐based procedures. Overall, 107 metabolites were found differentially regulated among genetically modified cells. Quantitative analysis has shown a significant modulation in DHNA‐CoA, p‐aminobenzoic acid, and citrulline levels, indicating an alteration in vitamin K, folic acid biosynthesis, and urea cycle of E. coli cells during heterologous gene expression. Modulations in energy metabolites including NADH, AMP, ADP, ATP, carbohydrate, terpenoids, fatty acid metabolites, diadenosine tetraphosphate (Ap4A), and l ‐carnitine advocate major metabolic rearrangements. Our study provides a broader insight into the metabolic adaptations of bacterial cells during gene manipulation experiments that can be prolonged to improve the yield of heterologous gene products and concomitant production of valuable biomolecules. Abstract : Our study provides a broader insight into the metabolic adaptations of bacterial cells during gene manipulation experiments that can be prolonged to improve the yield of heterologous gene products and concomitant production of valuable biomolecules. In the bacterial metabolite pathway figure. X ‐axis represents the impact of the identified metabolites on the indicated pathway. Y‐ axis indicates the extent to which the designated pathway is enriched in the identified metabolites. All the values were ascertained from MetaboAnalyst. Circle colors (see color scale for reference) indicate pathway enrichment significance. Circle size indicates pathway impact.